IMPLEMENTATION OF NANO COATING CERAMICS TECHNOLOGY IN VOCATIONAL LEARNING TO IMPROVE THE CORROSION RESISTANCE OF AUTOMOTIVE COMPONENTS IN COASTAL AREAS - Budiyanto; Fahmy Zuhda Bahtiar; Muhammad Rizky Rohmawan; Sena Mahendra; Wahid Bagas Wara; Yansen Capriano; Gigih Mujiyono (Universitas Negeri Semarang, 2025)
Coastal flooding creates a highly corrosive environment that damages motorcycle components. This study evaluates the synergistic effects of proper repainting procedures and nano-ceramic coatings on the corrosion resistance of the main standard of motorcycles. Laboratory experiments were conducted using a post-assay-only control group design with four treatments: nanocoating, repainting, a combination of both, and untreated controls. The samples underwent accelerated corrosion testing through immersion for 15 days in a 3.5% NaCl solution. The combined treatment shows superior performance, achieving the lowest corrosion rate (0.15 mm/year), perfect adhesion (0B), and highest hardness (4H). This represents a reduction in corrosion rate of about 91% compared to control. The results significantly show that integrating a multi-layer repainting foundation (primer, surfacer, top layer) with a SiO₂-based nano-ceramic top layer creates a synergistic barrier system. This approach is recommended as a highly effective and practical solution to significantly extend the life of assets and improve operational safety in corrosion-prone areas.